Peningkatan Kemampuan Pemecahan Masalah Siswa SMK melalui Model Problem-Based Instruction (PBI) - Rahmat Fitra; Hajidin Hajidin; Bansu Irianto Ansari (Universitas Syiah Kuala, 2016)
Problem-Based Instruction (PBI) is one of learning model which required student to be more active and create steps in solving problem so that the student should be able to develope their ability in solving mathematics problem and change the students perspective in mathematics positively. This study aims to asses the improvemement of problem solving and students self-concept that are taught by using PBI model and the student who taught by conventional learning through their level in studying. This study used pre-test post-test control group design. The population in this study is the eleventh grade students of SMK Farmasi Cut Meutia Banda Aceh in the school year 2013-2014. Samples were taken two classes XIA as the experimental class and XIB as a control class through purposing sampling technique. The instrument used to obtain research data is a mathematics problem solving ability test. The statistical test used to analyze the increasing problem solving data are ANOVA two path test. The result showed that the improvement problem solving ability that were taught by using PBI is better than students taught with conventional learning. According to students level, improving problem solving ability through PBI model is also better than students taught with conventional learning.